The psychological and performance demands of association football refereeing - Mascarenhas, Duncan; O'Hare, David; Plessner, Henning (International journal of sport psychology, 2006)
Traditionally, sports officials have only received a modicum of attention in sport science research literature. Perhaps more surprisingly, only recently have researchers begun to investigate key aspects of refereeing performance such as making judgments, communication behaviors and decision-making training interventions. With this in mind, we have reviewed the available empirical research into football officiating performance and where necessary drawn upon other research and applied programs of investigation in other sports. This paper is structured around the following key elements of referee performance; (1) judgment of offside; (2) judgment of fouls and misconduct; (3) control of game procedures; (4) management of the game and refereeing style; and (5) training complex high-performance skills that could be applied to the development of football refereeing. We highlight some of the demands of football refereeing, review the important findings and, with increasing interest in this area, provide suggestions to stimulate further research.